2018
DOI: 10.1371/journal.pone.0204279
|View full text |Cite
|
Sign up to set email alerts
|

Multiple genomic regions influence root morphology and seedling growth in cultivated sunflower (Helianthus annuus L.) under well-watered and water-limited conditions

Abstract: With climate change and an ever-increasing human population threatening food security, developing a better understanding of the genetic basis of crop performance under stressful conditions has become increasingly important. Here, we used genome-wide association studies to genetically dissect variation in seedling growth traits in cultivated sunflower (Helianthus annuus L.) under well-watered and water-limited (i.e., osmotic stress) conditions, with a particular focus on root morphology. Water limitation reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 124 publications
1
33
1
Order By: Relevance
“…To address these questions, we selected a set of 10 cultivated sunflower genotypes (Table ), varying broadly in biomass based on prior work, from a larger diversity panel used for genomic dissection of traits (Mandel et al., 2011; Masalia et al., 2018; Nambeesan et al., 2015). We conducted a factorial design of two nutrient treatments (rich and poor) and two light treatments (sun and shade) at the Botany greenhouses of The University of Georgia, Athens GA, USA, in March 2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these questions, we selected a set of 10 cultivated sunflower genotypes (Table ), varying broadly in biomass based on prior work, from a larger diversity panel used for genomic dissection of traits (Mandel et al., 2011; Masalia et al., 2018; Nambeesan et al., 2015). We conducted a factorial design of two nutrient treatments (rich and poor) and two light treatments (sun and shade) at the Botany greenhouses of The University of Georgia, Athens GA, USA, in March 2018.…”
Section: Methodsmentioning
confidence: 99%
“…To add to our understanding of plant responses to resource limitation, we examined trait responses to light and nutrient limitation of traits across different trait categories (biomass allocation, morphology, and anatomy) and organs (leaf, stem, and root) in cultivated sunflower. Prior research has shown strong plastic responses to resource limitation and other environmental factors in H. annuus (Bowsher et al., 2017; Donovan et al., 2014; Masalia et al., 2018; Rico et al., 2013; Temme et al., 2019). Specifically, we sought to answer the following questions: How do mass allocation, organ morphology, and anatomy change with above‐ and belowground resource limitation, and what role does size scaling of traits play in this? How do traits compare for magnitude of plasticity and what role does size scaling of traits play in this? Do traits show a coordinated shift due to resource limitation across all organs and what role does size scaling of traits play in this? …”
Section: Introductionmentioning
confidence: 99%
“…Twenty inbred genotypes (Table S1), including elite varieties and landraces, of cultivated sunflower (Helianthus annuus L.) were selected from a diversity panel, sunflower association mapping (SAM) population of 288 genotypes (Mandel, Dechaine, Marek, & Burke, 2011;Nambeesan et al, 2015). Genotypes were selected based on their differential responses in previous abiotic stress studies (Bowsher et al, 2017;Masalia, Temme, Torralba, & Burke, 2018). Plants were grown in a split-plot design with four replicates per treatment and genotype at the Plant Biology Greenhouse on the University of Georgia campus located in Athens, GA, from September to October of 2016.…”
Section: Methodsmentioning
confidence: 99%
“…GWAS was successfully implemented to many plant species including sunflower. In the case of sunflower, GWAS gave a new insight into flowering time (Bonnafous et al, 2018), male fertility restoration , seedling growth (Masalia et al, 2018), plasticity of oil yield for combined abiotic stresses (Mangin et al, 2017), basal and apical branching (Nambeesan et al, 2015), flower morphological traits (Dowell et al, 2019), and others.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%